Price efficiency of stock index futures contracts: are there any arbitrage opportunities? - Ramadilli Mohd, Shamsher Mohamad; Hasan, Taufiq (Universiti Putra Malaysia Press, 2000)
A futures contract is an agreement between a seller and a buyer that calls for the seller to deliver to the buyer a specified quantity and grade of an identified commodity, at a fixed time in the future, and at a price agreed in the contract. Stock index futures contract specify an equity index as the underlying asset. Arbitrage opportunity exists when the actual futures price deviates from the fair price by more than transactions costs. This study measures the arbitrage opportunities on the daily FKLI contracts price from calendar years 1996 through 1999. The pricing efficiency of the futures contracts was determined by the standard error between the closing actual and theoretical fair values for each month FKLI futures contract, where the theoretical value was estimated using the cost-of-carry model. The findings show that the actual futures prices do not converge towards theoretical prices with the passage of time. Arbitrage opportunities are related concepts. The fair price of a futures contract is determined by a pricing model that incorporates the value of the underlying cash asset, the time to expiration of the futures contract, the cost of financing the cash position, the cash inflows of the asset, and any special characteristics of the futures contract at expiration. In perfect markets - that is, when transactions costs and tax effects are not relevant - the actual futures price equals the fair price. Real futures markets are not perfect and there will always be opportunities to arbitrage the differences in the fair and actual prices of futures contracts and in the process aligning these prices, while earning arbitrage profits. The research issue addressed in this paper is whether arbitrage opportunities exists on the FKLI contracts and whether the futures market is price efficient over time.